Kebijakan peningkatan kualitas pelayanan kesehatan masyarakat miskin di Kabupaten Probolinggo - Irtanto Irtanto; Slamet Hari Sutanto (Universitas Merdeka Malang, 2019)
This research uses the concurrent embedded design approach. The objective of this research is to identify the regional regulation of Probolinggo Regency in the health sector in an effort to improve the quality of lower-class health services and the factors or obstacles in the implementation of health policies as well as to know the quality of the health services delivered to that poor community. The results show that the provision of lower-class health services is in the form of JKN membership (Jaminan Kesehatan Nasional or National Health Insurance) held by BPJS (Badan Penyelenggara Jaminan Sosial or Social Security Agency) in the health sector through PBI (Penerima Bantuan Iuranor Beneficiaries); Jamkesda (Jaminan Kesehatan Daerah or Regional Health Insurance) funds sharingparticipants; through a statement of incapacity (SKTM or Surat Keterangan Tidak Mampu). In this matter, the policy is in the form of Regent Decree number 12 of 2015 concerning the lower-class health services which are not included in JKN and Jamkesda at RSUD Waluyo Jati Kraksaan Probolinggo (Waluyo Jati Kraksaan Probolinggo Regional Public Hospital). The factor which becomes the obstacle in the policy implementation is the lack of specialist doctors such as a dermatologist and surgeon. The regional budget also becomes a barrier to meet various health facilities and infrastructure. Besides that, the problem from the lower class itself is the reluctance of the family to be referred to a government hospital (East Java Province) due to their incapability to meet the living and transportation expenses while they wait for the patient. Therefore, quantitatively, the policy implementation to improve the lower-class health services is able to make a positive contribution to the quality of health services in a public hospital. It is also known that various variable indicators are in a good category. Nevertheless, certain indicators still not good and need deep improvements in the service.DOI: https://doi.org/10.26905/pjiap.v4i1.2343